On a new Temnocephala (Platyhelminthes) from Southern Patagonia (Chile, Argentina), with a redescription of T. chilensis and some systematic and biogeographical insights - de León, Rodrigo Ponce; Rudolph, Erich H.; Volonterio, Odile (Zootaxa, 2020)
To date, only one species of Temnocephala is known from Chile, Temnocephala chilensis, and three from southern Argentina (Patagonia), namely T. chilensis, Temnocephala dionii, and Temnocephala mexicana. Here we describe a new species of Temnocephala and provide an updated description of T. chilensis based on material found on an anomuran crab (Aeglidae) from southern Chile. Additional hosts and localities are reported for both species in southern Argentina and Chile, and a diagnostic key for all species of Temnocephala hosted on Aegla and Parastacidae is included as well. In southern Chile, both T. chilensis and the new species were found on the crayfish Samastacus spinifrons and on the anomuran crabs Aegla abtao and Aegla alacalufi; in addition, the new species was found on Aegla manni, and T. chilensis on Aegla rostrata. In southern Argentina, T. chilensis and the new species were found on Aegla riolimayana and S. spinifrons. Based on their shared traits (morphology of the penial stylet, host preferences and geographic distribution), the temnocephalans hosted in Aegla are tentatively gathered into two clusters, the Chilensis and Axenos groups.